Improving the Ability to Use Punch Marks in Short Texts Using the Talking Stick Method for Students - Prastyaningsih, Hasti; Yani, Juli; Anggraini, Nori (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study focuses on the understanding of punctuation in short story writing skills with the aim of knowing the improvement of the ability to use punctuation in short story texts using the talking stick method in class IX students of SMPN 27 Tangerang City. The research method used in this study used Classroom Action Research (CAR). CAR makes it easier for educators to conduct research in finding out problems that occur in the classroom and finding solutions to problems found before and during the research. This study was carried out in three stages, namely pre-cycle, cycle I, and cycle II. The research instrument in the study was assisted by using an analysis table containing the results of improving students' abilities in each cycle. The data collection techniques used were tests and field notes. The data that had been collected were then reviewed based on the findings of the use of punctuation in each sentence used by students in writing short story texts. The sample in this study was 35 class IX students of SMP Negeri 27 Tangerang City.